Shock Thermal Resistance of Parachute Fabrics - Jiří Militký; Jakub Wiener; Dana Křemenáková; Mohanapriya Venkataraman (Eng)
The use of polyester and polyamide fabrics for parachute constructions has a great advantage because, in comparison with classical silk-based parachutes, they are more durable and suitable for absorbing higher mechanical shocks. Because polyester and polyamides are thermoplastics, they are sensitive to sudden increases in temperature due to mechanical shocks and high-speed friction. It is known that the local surface temperature of these parachute fabrics may exceed the melting point of the canopy for a short time period during parachute opening, which would have irreversible effects on parachute functionality and could lead to catastrophic parachute rupture. The main aim of this article is to enhance the surface heat resistance of the parachute fabrics from polyamide and polyester filaments through surface coating combined with super-fine TiO2 particles and silanization. This coating is also selected to increase the frictional heat loss and enhance the mechanical stability of parachute fabrics constructed from polyamide and polyester filaments. The changes in air permeability, bending rigidity, and friction of surface-coated parachute fabrics are evaluated as well. The new method based on laser irradiation by a pulsed laser is used for the prediction of these fabrics’ short-time surface thermal resistance.